Pengaruh Parameter Green Sintesis TiO₂ Berbasis Metode Solvotermal terhadap Ukuran Partikel dan Ukuran Kristal: A Systematic Review - Dian Wijaya Kurniawidi; Kormil Saputra; Nur Azzahra Al Radhiyah; Indrawan Eka Badri; Ika Umratul Asni Aminy (MASALIQ, 2026)
Titanium dioxide (TiO₂) is a semiconductor material widely used in photocatalysis, sensor, energy conversion, and environmental remediation applications because its performance is strongly influenced by structural characteristics, particularly particle size, crystal size, morphology, and crystal phase. This systematic review aims to analyze the influence of green synthesis parameters based on the solvothermal method on the particle size and crystal size of TiO₂. Articles were collected from the Scopus, ScienceDirect, and Google Scholar databases within the 2021–2025 publication range using combinations of Boolean keywords related to solvothermal synthesis, TiO₂, and green synthesis. Article selection was conducted based on inclusion and exclusion criteria emphasizing original research articles, the use of the solvothermal method, a green synthesis approach, and the availability of material characterization data. The review results showed that four articles met the inclusion criteria, with variations in TiO₂ particle size ranging from 25.41 to 100 nm and crystal size ranging from 0.96 to 31.9 nm. Parameters such as precursor type, solvent, green extract, solvothermal temperature, and processing time played important roles in regulating nucleation, crystal growth, surface stabilization, and particle agglomeration. The smallest particle size was obtained in the titanium isopropoxide–deionized water–banana peel system at 100 °C, whereas modified systems such as Ag-doped TiO₂ and TiO₂@g-C₃N₄ showed that application performance is determined not only by particle size but also by electronic engineering and interface structure. The conclusion of this review affirms that the optimization of green solvothermal synthesis of TiO₂ needs to be directed toward integrated control of particle size, crystal size, crystal phase, morphology, and application performance. The implications of this review contribute to the development of more targeted, efficient, and relevant green TiO₂ synthesis for sustainable functional material applications.